Port of New York - Benedek, Laslo, 1905-1992; Ling, Eugene; Townsend, Leo, 1908-1987; Brady, Scott, 1924-1985; Brynner, Yul; Contemporary Productions, Inc.; Cinetel Films ([Los Angeles, CA] : Contemporary Productions, Inc., 1949)
A drug smuggler runs his operation through a New York yacht club, spreading his criminal operation through the use of ocean liners and their staff, to distribute the narcotics. A pair of undercover agents is assigned to track down the source of the narcotics and bring down the drug ring. To get to the criminals, the agents must go under cover to infiltrate the gang, which places them in greater peril the closer they get to the ringleader.
Originally released as a motion picture in 1949.
Scott Brady, Richard Rober, K.T. Stevens, Yul Brynner, Arthur Blake, Lynne Carter, John Kellogg, William Challee.
Cinematographer, George E. Diskant; editor, Norman Colbert; music, Sol Kaplan; musical director, Irving Friedman.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Drug control -- New York (State) -- New York -- Drama; Undercover operations -- New York (State) -- New York -- Drama; Feature films; Gangster films; Crime films; Internet videos; Streaming video